2020
DOI: 10.1016/j.devcel.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

PRL3-DDX21 Transcriptional Control of Endolysosomal Genes Restricts Melanocyte Stem Cell Differentiation

Abstract: Summary Melanocytes, replenished throughout life by melanocyte stem cells (MSCs), play a critical role in pigmentation and melanoma. Here, we reveal a function for the metastasis-associated phosphatase of regenerating liver 3 (PRL3) in MSC regeneration. We show that PRL3 binds to the RNA helicase DDX21, thereby restricting productive transcription by RNAPII at master transcription factor (MITF)-regulated endolysosomal vesicle genes. In zebrafish, this mechanism controls premature melanoblast expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 91 publications
(113 reference statements)
2
37
0
Order By: Relevance
“…In addition, DDX21 was found to regulate transcription in melanocyte stem cells (McSCs) in the hair follicle bulge to prevent differentiation into melanocytes. 76 There has been much debate recently about whether the cell at the origin of melanoma indeed represents a stem cell-like cell. In fact, the above-mentioned studies somewhat stand in contrast to reports claiming that instead of cells with stem cell features, fully differentiated melanocytes can give rise to melanoma.…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DDX21 was found to regulate transcription in melanocyte stem cells (McSCs) in the hair follicle bulge to prevent differentiation into melanocytes. 76 There has been much debate recently about whether the cell at the origin of melanoma indeed represents a stem cell-like cell. In fact, the above-mentioned studies somewhat stand in contrast to reports claiming that instead of cells with stem cell features, fully differentiated melanocytes can give rise to melanoma.…”
Section: Significance Statementmentioning
confidence: 99%
“…Mechanistically, DHODH inhibition‐induced nucleotide stress has recently been linked to the RNA helicase DDX21, which senses nucleotide shortage in NCSCs as well as melanoma cells, upon which it stops transcriptional elongation 45 (Table 1). In addition, DDX21 was found to regulate transcription in melanocyte stem cells (McSCs) in the hair follicle bulge to prevent differentiation into melanocytes 76 …”
Section: Developmental Ncsc Genes Regulate Melanoma Growth and Homeosmentioning
confidence: 99%
“…How to make the melanocytes cease to quiescent condition and reenter the cell cycle is the biggest challenge in melanocytes regeneration. It has been reported that the Kit receptor tyrosine kinase is essential for the regeneration of zebrafish larval melanocytes [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…PRL-3, in particular, has been identified as a potential cancer biomarker (1). PRL-3 expression was first identified as significantly upregulated in metastatic colorectal cancer, compared to primary lesions and normal tissue (2); since, PRL-3 has been implicated in progression and metastasis in gastric (3), ovarian (4), breast(5), brain (6), and prostate (7) cancers, melanoma (8) (9), and leukemias (10) (11). Experimental evidence indicates that PRL-3 expression increases proliferation, migration, and invasion of cancer cells in vitro (12) (13) (14) and enhances tumor growth and metastasis in mouse models (2) (15), while PRL-3 knockdown significantly suppresses tumor formation and spread in vivo (16).…”
Section: Introductionmentioning
confidence: 99%